Precocious Puberty- A Case Report - Shah, K Kabiruzzaman; Laz, N Begum; Siddique, AB; Ahmed, FU (TAJ: Journal of Teachers Association, 2009)
Appearance of secondary sexual development before the age of 9 in a male child and before the age of 7 in a female child is called precocious puberty. When the cause of precocious puberty is premature activation of the hypothalamic-pituitary axis, it is called central or complete precocious puberty, if ectopic gonadotrophin secretion occurs in boys or autonomous sex steroid secretion occurs in either sex it is called incomplete precocious puberty. |Here we are reporting a 5 year old girl with central precocious puberty. doi: 10.3329/taj.v21i1.3227 TAJ 2008; 21(1): 83-86